Legal Framework and Law Enforcement of Illegal Fishing in Indonesia: A Normative Juridical Approach to the Protection of Maritime Sovereignty - Rahmawati, Diah Ayu; Hartantien, Sinarianda Kurnia; Kumalasari, Dewi Ratih; Haryono, Haryono; Endarto, Budi (West Science Law and Human Rights, 2025)
The paper will attempt to discuss illegal fishing in Indonesia from a legal framework and law enforcement perspective and its implications for the protection of maritime sovereignty. Based on this, the research will apply a normative juridical approach, studying in detail the laws, regulations, and practices of enforcement and the various challenges and opportunities arising out of them. Indnesia legal framework through the Fisheries Law no 45 of 2009 and the Presidential Decree no. 115 of 2015 set a good backbone regarding IUU fishing activities; still, poor enforcement is highly seen due to shortcomings in limited resources, corruption, fragmented jurisdiction, and less international cooperation. The paper analyses these discrepancies and assesses Indonesia's current legislation and the efforts carried out on tackling IUU in comparison to relevant international practices. It also gives some recommendations on how to strengthen the legal definition, mechanisms of enforcement, increasing resource allocations, and improvement in international cooperation. The result shows that integrated efforts with more transparency and accountability are needed in order to properly protect Indonesia's maritime sovereignty effectively.